Inovasi Pedagogi dan Model Pembelajaran dalam Pendidikan Islam Kontemporer - Ainul Yakin; Misbahul Arifin; Tiara Nurul Anisa; Toyyibatul Mukminatus Sukriyah; Ulfa Qomariatul Jannah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explore and analyze pedagogical innovation practices and learning models at MTs Darul Musthofa, Probolinggo, within the context of contemporary Islamic education. The research focuses on the integration of digital technology, teacher collaboration, and the internalization of pesantren values in the learning process. Employing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, and documentation. The findings indicate that the madrasah successfully developed an innovative learning ecosystem that combines digital media with pesantren traditions, such as the use of Google Classroom, digital lesson plans, student blogs, and interactive Islamic content. These practices enhance students’ digital literacy while maintaining the religious character that underpins the institution. The implications suggest that Islamic educational institutions, even in rural areas, can adopt transformative learning models based on technology and local values synergistically. This research is expected to serve as a reference for the development of policies and Islamic education models that are adaptive to contemporary challenges.